A study on the wing-loading and aspect-ratio for fruit bats of family pteropodidae - Vijaya, Menon (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study was conducted as an attempt to describe habitat use by fruit bats from data analysis of wing-loading and aspect-ratio. Study of wing-loading and aspect-ratio was successful in describing habitat use of fruit bats. The study revealed that the family Pteropodidae had relatively high wing-loadings and low aspect-ratio. There were also high degree of overlap in wing-loading and aspect-ratio within the fruit bat family which indicated overlap in habitat usage. Species that were of low wing-loading and aspect-ratio are able to use both cluttered and uncluttered habitat. This could be a strategy to reduce competition. Where else, species with higher wing-loading and aspect-ratio are only confined to uncluttered habitat. The value of these flight indices were also related to the load the bats carry and the distance they travel. Wing-loading and aspect-ratio were able to explain the flight behavior such as maneuverability, speed and agility of the animal.